"This is oil country:" mediated transnational girlhood, Greta Thunberg, and patriarchal petrocultures. Issue 4 (19th May 2021) - Keller, Jessalynn
ABSTRACT: In this short reflection piece I consider Greta Thunberg as a figure of mediated transnational girlhood whose "spectacular" visibility which circulated through global media networks reveals the sexist, racist, and ageist underpinnings of Alberta's local oil culture. I begin to parse the mediated relationship between Thunberg and Alberta's oil culture through the exploration of two examples of mediated misogyny, a sticker that seemingly depicts the teen being sexually assaulted, and an artistic street mural that was defaced by pro-oil activists, both which began as local responses to Thunberg, but quickly circulated globally via international news media and social media users. I suggest that these disturbing examples function as anxious local reactions to the perceived threats posed by the transnational figure of Thunberg, which challenge not only colonial and patriarchal promises of land ownership and resource extraction, but hegemonic ideas about girlhood and the future more generally.